The Association Between Long-Term Exposure to Particulate Matter and Incidence of Hypertension Among Chinese Elderly: A Retrospective Cohort Study - Wensu, Zhou; Wen, Chen; Fenfen, Zhou; Wenjuan, Wang; Li, Ling (Frontiers in Cardiovascular Medicine, 2022)
Background and Objectives: Studies that investigate the links between particulate matter less than or equal to 2.5 um (PM2.5) and hypertension among the elderly included aged over 80 years, are limited. We aimed to examine the links between PM2.5 exposure and hypertension incidence risk among Chinese elderly. Methods: This prospective cohort study used 2008, 2011/2012, 2014 and 2018 wave data from the Chinese Longitudinal Healthy Longevity Survey, a national survey investigating the elderly aged over 65 years in China. We enrolled participants who were free of hypertension at baseline (2008) from 706 counties (districts) and collected data from the 2011/2012, 2014, and 2018 survey waves. The annual PM2.5 concentration of 706 counties (districts) units was derived from the Atmospheric Composition Analysis Group database as the exposure variable. A Cox proportional hazards model with penalized spline was used to explore the nonlinear association between PM2.5 concentration and hypertension risk. A random-effects Cox proportional hazards model was built to explore the relationship between each 1 μg/m3, 10 μg/m3 and quartile increment in PM2.5 concentration and hypertension incidence after adjusting for confounding variables. The modification effects of the different characteristics of the respondents were also explored. Results: A total of 7432 elderly aged 65–116 years were enrolled at baseline. The average 1-year window period of PM2.5 exposure before the onset of hypertension has the greatest risk for hypertension incidence. There was no safe threshold for PM2.5 exposure. Each 1 μg/m3 (adjusted hazard ratio (AHR): 1.03; 95% CI: 1.02-1.03) and 10 μg/m3 (AHR: 1.27; 95% CI: 1.22-1.32) increments in PM2.5, were links with the incidence of hypertension. Compared to first quartile (Q1) exposure, the adjusted HRs of hypertension incidence for the Q2, Q3 and Q4 exposure of PM2.5 were 1.33 (95% CI: 1.15-1.55), 1.56 (95% CI: 1.32-1.86) and 2.69 (95% CI: 2.24-3.24), respectively. The effects were stronger among those without a pension, living in a rural setting, located in central/western regions, and with a body mass index < 18.5. Conclusion: We found no safe threshold for PM2.5 exposure related to hypertension risk, and more rigorous approaches for PM2.5 control are needed.